Integrated design optimization of structural topology and heat source layout. (April 2021) - Wang, Yaguang; Luo, Yangjun; Kang, Zhan
Highlights: A optimization method for integrated design of structural topology and heat source layout is proposed. A multi-objective function combining both mechanical and heat transfer performances is considered. The velocity field level set method is used to handle multiple constraints and multiple types of design variables in the integrated design problem efficiently. The level set model provides a relatively smooth representation of the material interfaces and facilitates implicitly tracking the layouts of the embedded components. The continuity conditions at the component interfaces are considered in the sensitivity analysis Abstract: Heat source devices embedded in a multi-component structural system are often used as integrated load-bearing components to fulfill multi-functionality and lightweight requirements. This paper proposes a multi-objective topology optimization method for integrated layout design of such multi-component structures. The layout of heat sources and the topology of host structure are optimized simultaneously to improve the structural stiffness and heat transfer performance. The velocity field level set method, which offers a convenient way to handle multiple constraints and general design variables in the implicit boundary description-based topology optimization framework, is employed in the formulation of the optimization problem. Therein, the level set model provides a relatively smooth representation of the material boundary and structure/component interfaces, and also facilitates implicitly tracking the layouts of the embedded components. An adjoint-variable sensitivity analysis scheme is derived by considering the continuity conditions on the structure/component interfaces. Several numerical examples are presented to demonstrate the validity and efficiency of the proposed framework.